If the value of the summation above can be expressed as , where and are coprime positive integers, find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is clear from the given expression that we need to deal with the expression 9 x + 3 9 x . So let us consider the expression in the form of a function.
Let f ( x ) = 9 x + 3 9 x .
⇒ f ( 1 − x ) = 9 ( 1 − x ) + 3 9 ( 1 − x ) = 9 + ( 3 ) ( 9 x ) 9 = 9 x + 3 3 .
⇒ f ( x ) + f ( 1 − x ) = 9 x + 3 9 x + 9 x + 3 3 = 1 .
Also, clearly f ( 2 1 ) = 2 1 .
The required sum is, f ( 2 0 0 0 1 ) + f ( 2 0 0 0 2 ) + ⋯ + f ( 2 0 0 0 9 9 9 ) + f ( 2 0 0 0 1 0 0 0 ) + f ( 2 0 0 0 1 0 0 1 ) + ⋯ + f ( 2 0 0 0 1 9 9 9 )
= f ( 2 0 0 0 1 ) + f ( 2 0 0 0 2 ) + ⋯ + f ( 2 0 0 0 9 9 9 ) + f ( 2 1 ) + f ( 1 − 2 0 0 0 9 9 9 ) + ⋯ + f ( 1 − 2 0 0 0 1 ) = r = 1 ∑ 9 9 9 ( f ( 2 0 0 0 r ) + f ( 1 − 2 0 0 0 r ) ) + f ( 2 1 )
= ( 9 9 9 ) ( 1 ) + 2 1 = 2 1 9 9 9 ⇒ b a = 2 1 9 9 9 ⇒ a + b = 2 0 0 1